Gambaran Penderita Fraktur Maksilofasial di RSUD Arifin Achmad Pekanbaru Periode Januari 2009-desember 2011 - Nanda juwita; Welli Zulfikar; Tuti Restuastuti (Jurnal Ilmu Kedokteran, 2011)
Maxillofacial fracture can cause facial deformity up to threat life saving thing due to disturbance of airway. Maxillofacialfracture is most happen in productive age because of more high activities. This research purpose to know thedemography maxillofacial fracture patient. This research was a descriptive retrospective study which was done atArifin Achmad General Hospital Pekanbaru. Base on secondary data research results that take from patient’s medicalrecord from 195 patients maxillofacial fracture, only 135 cases include to criteria. Maxillofacial fracture 117 patientswere men (86,67%) and 18 patients were women (13,33%). Most of patients were 11-20 years old 53 cases (39,26%).Traffic accident was the most etiology maxillofacial fracture 128 cases (94,81%.). Most often clinical manifestationswere edema of soft tissue, epistaxis, deformity and malocclusion. Mandibula fracture as the first top case were 62patients (45,92%). Surgery (ORIF) was mostly done in 87 patient (64,45%), include combine with close reduction.